Analisis Kompetensi Guru Mata Pelajaran Produktif Pada SMK Negeri di Kota Makassar - Akbar Subharsa; Rusyadi; Faizal Amir (UNM Journal of Technology and Vocational, 2021)
This study is a quantitative descriptive research that aims to describe the teachers’ competency in productive subject at SMKN (public vocational schools) in Makassar city. The research variables are pedagogic competence, personal competence, social competence, and professional competence. The population of the study was 223 teachers in productive subject spread from 13 SMKN in Makassar City, the sample was chosen by employing systematic random sampling technique and obtained 70 teachers in productive subject. The study employed quantitative descriptive analysis method. The research data were obtained from the Makassar DISDIK documentation. The results of the study reveal that the average value of pedagogic competence is 48.90 (24.73%), the average value of personal competence is 47.59 (24.07%), the average value of social competence is 51.71 (26.16%), and the average value of professional competence is 49.51 (25.04%). The conclusion based on the value of pedagogic competence, personal competence, social competence, and professional competence, the teachers’ competency in productive subject at SMKN in Makassar city is in low category.